The effect of physical therapy rehabilitation on fatigue and pain in female patients with fibromyalgia - Nada Gamal Abdelaziz; Gehan Mahmoud Ramzy; Hala Lotfy Fayed; Sara M. Ahmed; Gehan Mousa Ahmed (Universidad de Murcia, 2024)
Article accepted. The article will be published here soon. Pending final quality checks.